Considerations of the Malaysian Standards Council in Setting Quality Standards Malaysian Standards (MS 1900:2005) - Halmahera, Adityas (ITQAN: Journal of Islamic Economics, Management, and Finance, 2023)
This study provides an overview of the Malaysian Standards Council's considerations in establishing the quality standard Malaysian Standard 1900 (MS 1900, p. 2005). MS 1900 is a structured system that helps organizations to provide products and services that suit customer requirements based on Sharia regulations and requirements. This system was launched in 2005 and aimed to complement the ISO 9001 standard concerning an Islamic perspective. To obtain this MS 1900, the organization must go through a process of quality audit and sharia audit. Various kinds of literature were reviewed, focusing on the Malaysian Quality Management Standard MS 1900:2005. This research found that the Sharia elements were synchronized into the existing ISO 9001 to establish the first Islamic quality management system, MS 1900:2005. MS 1900:2005 not only helps organizations improve their management systems but also enables organizations to implement management systems per Shariah and Islamic obligations. The proposed model should be followed by managers so that MS 1900:2005 can be implemented effectively.